In-situ generation of spherical aggregates of Pd nanoparticles on the surface of poly(acrylic acid)-grafted MWNTs containing POSS. (13th August 2017) - Hwang, In Seol; Lim, Jung-Hyurk; Kim, Ki-Young; Kim, Kyung-Min
ABSTRACT: PAA-grafted MWNTs containing POSS (POSS/PAA-grafted MWNTs) were synthesized by the simple mixing of octa(3-aminopropyl)octasils-esquioxane (POSS-NH3 + ) and PAA-grafted MWNTs via ionic interactions. The spherical aggregates of Pd nanoparticles on the surface of POSS/PAA-grafted MWNTs (Pd-POSS/MWNTs) were produced with an average size of 10–20 nm due to the effect of POSS-NH3 + used as a cubic linker physically attached to PAA-grafted MWNTs. The size of Pd-POSS/MWNTs was smaller than that of spherical aggregates of Pd nanoparticles prepared by only POSS-NH3 + . The residual content of Pd-POSS/MWNTs is larger than that of POSS/PAA-grafted MWNTs because of the aggregates of Pd nanoparticles.